The Effect Of Plyometric And Tabata Training On Jump Performance, Respiratory Function Parameters On Aerobic Gymnasts - Gencay Cüce; Engin Güneş Atabaş; Ayşegül Yapıcı (Türk Spor ve Egzersiz Dergisi)
In this study, the effect of pliometric and tabata training applied to aerobic gymnasts between the ages of 12-14 on jump performance and respiratory function parameters was investigated. Actively competing in the study, mean age 12.8 ± 0.19 (year), average body weight 34.28 ± 1.46 (kg), average height 145.19 ± 2.29 (cm), average age for sports 7.14 ± 0.24 female gymnasts participated voluntarily. The subjects were randomly divided into 3 groups according to age groups. First group (A group), Technical + Pliometric training program, second group (B group), Technique + Tabata training program, third group (C group) control group applied only Technical training program. A total of 12 exercises were applied to the subjects for 6 weeks, 2 exercises per week. The subjects were tested for jump performance, 30 sec Bosco Test, respiratory function test and C group basic difficulty elements test, pre-test and post-test. In the evaluation of the data, analysis of variance was used in 3 x 2 repeated measures. The difference between the groups was determined by the Bonferroni test. As a result of the 6-week training, there was no significant difference in the control group according to the pre-test and post-test results, while in the pliometric training group and tabata training groups, active jump, 30 sec Bosco, tuck jump, cossack jump, pike jump and straddle jump group C There was a significant difference in performance, respiratory functions at FEV1 and FVC (p lt;0.05) levels, but no significance was found at other levels (p gt;0.05). As a result, it is recommended to trainers to use pliometric training for jumping strength and performance increase, tabata training method to increase the continuity of the series, reduce energy expenditure and increase anaerobic capacity.